Which thoracic curves are at the greater risk for distal adding-on: comparison between typical and atypical Lenke 1A curves - Yin, Rui; Qin, Xiaodong; He, Zhong; Liu, Zhen; Qiu, Yong; Zhu, Zezhang (European spine journal, 2021)
Purpose To identify the characteristics and the incidence of adding-on (AO) in atypical Lenke 1A adolescent idiopathic scoliosis patients, and to investigate whether atypical and typical Lenke 1A curve should follow the same lowest instrumented vertebra (LIV) selection strategy. Methods A total of 251 Lenke 1A patients who underwent posterior spinal fusion were analyzed. The minimum follow-up was 2 years. Curves were classified into two groups according to the apex. At last, 42 atypical Lenke 1A patients (apex at T10/11–T11/12) were identified and divided into atypical group (G1). Meanwhile, 42 age, gender, and Cobb angle-matched typical Lenke 1A patients (apex at T7/8–T10) were enrolled into the typical group (G2). The radiographic characteristics were evaluated, and the incidence of AO was compared between the 2 groups. Results The incidence of atypical Lenke 1A curves was 16.7%. Patients in G1 were found to have more left thoracic curves ( P = 0.029), better flexibility of thoracic ( P = 0.011) and lumbar curve ( P = 0.014), and more preoperative coronal imbalance ( P = 0.001). At the final follow-up, G1 developed more AO (38.1% vs. 19.0%). Specificity, for patients with LIV proximal to last substantially touching vertebra (LSTV), the incidence of AO was significantly higher in G1 (82.4% vs. 42.9%, P = 0.022). Conclusion Atypical Lenke 1A curve had its own radiographic characteristics. It was more likely to develop AO when LIV was proximal to LSTV, which indicated different fusion levels should be considered in these two subtypes of Lenke 1A. We recommended LSTV as LIV in atypical Lenke 1A cases, while one level proximal to LSTV might be available in typical Lenke 1A curve. Level of evidence 3